Features of the genesis of the avifauna on the border of Forest-Steppe and Steppe natural zones - Атемасова, Т. А.; Атемасов, А. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The analysis of dynamic of areas for some bird species at the Forest-steppe/Steppe boarder in the Northern-east of Ukraine are presented. The species extinted in the region during past 120 years since the publication of monografs by N.N.Somov and N.A.Zarudny have been determined. The some species, typical for the desert-steppe faunistical complex (such as Great Bustard, Little Bustard, Sociable Plover) have become absent completely. A process of immigration of new species, predominantly tropical faunistic group members (Great white Heron, Purple Heron, Black-crowned Night-heron, Lesser Spotted Eagle) occur now. Also restoration of areas of Ruddy Shelduck, Corn Bunting takes place. Anthropogenious transformation of habitats is a cause of populations decrease and change of status of some species.